The Influence of Javanese Cultural Appeal on Tourists' Decision to Stay at Lorin Solo Hotel in Surakarta - Febrian Krissetya Dharma; Dyan Triana Putra (International Journal of Economics and Management Research, 2026)
This study examines the influence of Javanese cultural appeal on tourists' decisions to stay at Lorin Solo Hotel in Surakarta, Central Java, Indonesia. Drawing on a structured literature review of 50 peer-reviewed studies combined with primary survey data from 120 hotel guests, the research identifies six key dimensions of cultural appeal: cultural authenticity, Javanese hospitality values, culinary experience, architectural design, cultural event programming, and city branding. Findings from multiple regression analysis reveal that cultural authenticity (β = 0.372, p < 0.001) and Javanese hospitality values (β = 0.315, p < 0.001) are the strongest predictors of tourists' decision to stay, collectively accounting for 68.1% of the variance in the dependent variable. Culinary experience and architectural design also show statistically significant positive effects. City branding, while positively associated, does not reach statistical significance when other cultural dimensions are controlled. The study concludes that authentic, deeply integrated Javanese cultural elements—rather than superficial aesthetic decoration—are decisive factors in attracting and retaining guests at culturally themed heritage hotels. Implications for hotel management strategy and destination branding in Surakarta are discussed, along with recommendations for future research.